Perancangan Aplikasi Manajemen Transaksi Terintegrasi Di PT Nearby Digital Indonesia - Arzyah, Muhammad Fikri; Abdillah, Adrian; Putra, Ade Dwi; Khaerunnisa, Fairuz Syifa; Samsoni, Samsoni (Universitas Muhammadiyah Gorontalo, 2023)
With the rapid development of technology in today's digital age, can increase profits and expand the reach of their business. After the Internet came, this development happened very quickly. Businessmen can now trade their goods in a new way provided by the Internet, called e-commerce. Mobile apps and websites are one of the most popular forms of information technology and are easily accessible by many people. In this study, data is collected through observation and direct review of the research site to find out the condition at PT Nearby Digital Indonesia. In addition, we use a library study method, which collects data through references from various sources, including articles and journals related to this research. After evaluating the research system, the researchers proposed a sales information system. Better systems will make it easier for employees to manage data and transaction reports. Data Processing Efficiency: PT Nearby Indonesia can process transaction data easily thanks to its planned information system. The process of recording transaction data is done automatically, which saves time and avoids human error. In addition, the easy-to-do merging and calculation of transaction data with this system speeds up the processing process.